Palmar Dermatoglyphic Patterns of Female b Thalassemia Major Patients in Bangladeshi Population - Zahan, Afroj; Naushaba, Humaira; Paul, Uttam Kumar; Islam, AHM Mazharul; Moin, Sharna; Jebin, Suraiya (Bangladesh Journal of Anatomy, 2019)
Context: Dermatoglyphics have proven to be a helpful tool in identifying specific syndromes of genetic origin. Many studies were carried out in different parts of the world where comparison between dermatoglyphic patterns of female b thalassemia major patients with normal individuals were done. Unusual dermatoglyphic patterns were reported in b thalassemia major patients. So far it is known, there is no published article on this topic in Bangladesh. This study was aimed to establish a standard baseline data of the palmar dermatoglyphic patterns of female b thalassemia major patients in Bangladesh and to make comparison with healthy individuals. Materials and Methods: This cross sectional study with some analytical component was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka, Bangladesh. This study recruited 25 b thalassemia major female patients and 31 healthy female individuals. Dermatoglyphic prints of the study subjects were taken by ink & paper method and then the palmar dermatoglyphic patterns on the distal phalanges of each hand were studied with 6X magnifying glass. The palmar dermatoglyphic patterns of the female b thalassemia major patients were observed and compared with the healthy individuals. Results: The palmar dermatoglyphic patterns of the female b thalassemia major patients were significantly different from that of the healthy female individuals (p < 0.05). Conclusion: This study concludes that palmar dermatoglyphic patterns can be useful in the management of female b thalassemia major patients specifically in early prediction & at the level of prevention. Bangladesh Journal of Anatomy January 2019, Vol. 17, No. 1, pp. 10-13